1991
DOI: 10.1021/tx00024a008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cytochrome P-450 2E1 by diallyl sulfide and its metabolites

Abstract: Diallyl sulfide, a major flavor ingredient from garlic, was previously shown to inhibit chemically induced carcinogenesis and cytotoxicity in animal model systems. It modulated cytochrome P-450 compositions by inactivating P-450 2E1 and inducing P-450 2B1. The present studies examined the inhibition of P-450 2E1 mediated p-nitrophenol hydroxylase activity by diallyl sulfide and its putative metabolites diallyl sulfoxide and diallyl sulfone (DASO2). Each compound displayed competitive inhibition of p-nitropheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
133
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(144 citation statements)
references
References 13 publications
9
133
2
Order By: Relevance
“…We initially hypothesized that CC14 metabolism and lipid peroxidation contribute to hepatocyte death in culture. However, in our system two different inhibitors of P450, cimetidine and diallyl sulfide (Nanji et al 1994;Brady et al 1991) reduced isoprostane accumulation by >8O%, almost to control levels, without an evident decrease in cell death. Kupffer cells probably also play an important role in promoting CC14 toxicity in vivo (Edwards et al 1993).…”
Section: Discussionmentioning
confidence: 54%
“…We initially hypothesized that CC14 metabolism and lipid peroxidation contribute to hepatocyte death in culture. However, in our system two different inhibitors of P450, cimetidine and diallyl sulfide (Nanji et al 1994;Brady et al 1991) reduced isoprostane accumulation by >8O%, almost to control levels, without an evident decrease in cell death. Kupffer cells probably also play an important role in promoting CC14 toxicity in vivo (Edwards et al 1993).…”
Section: Discussionmentioning
confidence: 54%
“…Nitrile dose selection was based on our previous data Saldaña-RuĂ­z et al 2012a). The selective CYP2E1 inhibitor DAS (Brady et al 1991) was administered p.o. in 6 ml/kg of corn oil; DAS acts as a competitive inhibitor of CYP2E1 and is also metabolized to suicide inhibitors of the same enzyme.…”
Section: Dosing and Experimental Protocolmentioning
confidence: 99%
“…A growing number of naturally occurring phytochemicals in foods and herbal supplements have been shown to be substrates or inactivators of P450 enzymes. Some examples include bergamottin, a component of grapefruit juice (He et al, 1998); capsaicin from chili peppers (Surh and Lee, 1995); diallylsulfide found in garlic oil (Brady et al, 1991); numerous isothiocyanates found in all cruciferous vegetables (Conaway et al, 1996;Goosen et al, 2000); I3,II8-bia-piogenin, hypericin, hyperforin, and other components of St. John's Wort (Orbach, 2000); roquefortine, a secondary cyclopeptide metabolite generated by Penicillium reoquefortine and other Penicillium species (Aniant et al, 2001); reservatol, a component of red wine (Chan and Delucchi, 2000); and thujones found in the liqueur absinthe (Höld et al, 2001).…”
Section: Liver Microsomal P450mentioning
confidence: 99%